Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

(1-w-w²)⁶=64 prove thta​

Sagot :

1−w−w2=64

Step 1: Simplify both sides of the equation.

−w2−w+1=64

Step 2: Subtract 64 from both sides.

−w2−w+1−64=64−64

−w2−w−63=0

For this equation: a=-1, b=-1, c=-63

−1w2+−1w+−63=0

Step 3: Use quadratic formula with a=-1, b=-1, c=-63.

w= −b±√b2−4ac /2a

w= −(−1)±√(−1)2−4(−1)(−63) /2(−1)

w= 1±√−251/ −2